Exploration of Wax Vegetable Plants (Saccharum edule) in West Halmahera Regency North Maluku Province - Fitri Wahyu Wijayanti; Stevani B Fara (Faculty of Agriculture, Pattimura University, 2019)
Waxed vegetable plants (Saccharum edule) have a variety of species, can be found in several regions in Indonesia. This study aims to determine the types of vegetable candles in West Halmahera Regency, North Maluku Province. The research was carried out in nine sub-districts, 36 villages and involved 108 farmer owners. Research uses exploration and identification methods. Variables observed included stem shape, stem color, stem length, and plant height, as well as the color and length of the flower. The results of the study found that there were five types of vegetable candles namely short white, long white, long yellow, short yellow, and long white with reddish tree trunks. The five types of plants can be found throughout the sub-districts in West Halmahera Regency, Maluku Province.Keywords: West Halmahera, Saccharum edule, Wax vegetable